Տավուշի բանասացության պատմությունից - Էսթեր Խեմչյան (ՀՀ ԳԱԱ հրատ.)
Развитие, хранение и передачу фольклорного материала осуществляют сказители. Сказители – одаренные индивидуумы, которые с детства росли в конкретной среде, питаясь фольклорной традицией. Они имеют блестящую память, умеют своеобразно воспроизвести выученное. Development, storage and transfer of folklore material is performed by story-tellers. They are gifted individuals who grew up from childhood in an environment full of folk traditions, have brilliant memory, and are able to reproduce originally the learned.
Keywords: G Geography; Anthropology; Recreation; GR Folklore; GT Manners and customs